2016
DOI: 10.1016/j.ejphar.2016.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Chronic β 1 -adrenoceptor blockade impairs ischaemic tolerance and preconditioning in murine myocardium

Abstract: β-adrenoceptor antagonists are commonly used in ischaemic heart disease (IHD) patients, yet may impair signalling and efficacy of ‘cardioprotective’ interventions. We assessed effects of chronic β1-adrenoceptor antagonism on myocardial resistance to ischemia-reperfusion (IR) injury and the ability of cardioprotective interventions [classic ischaemic preconditioning (IPC); novel sustained ligand-activated preconditioning (SLP)] to reduce IR injury in murine hearts. Young male C57Bl/6 mice were untreated or rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
(112 reference statements)
0
7
0
Order By: Relevance
“…A brief treatment of short-acting BB, esmolol, also attenuated the effects of ischemic preconditioning in rabbit hearts [14]. In addition, beta-adrenergic blockade with atenolol abrogated the beneficial effects of preconditioning in isolated mouse hearts [44]. However, retrospective analyses of clinical studies showed no impact of BB on RIPC-induced cardioprotection in patients undergoing CABG surgery [45].…”
Section: Discussionmentioning
confidence: 99%
“…A brief treatment of short-acting BB, esmolol, also attenuated the effects of ischemic preconditioning in rabbit hearts [14]. In addition, beta-adrenergic blockade with atenolol abrogated the beneficial effects of preconditioning in isolated mouse hearts [44]. However, retrospective analyses of clinical studies showed no impact of BB on RIPC-induced cardioprotection in patients undergoing CABG surgery [45].…”
Section: Discussionmentioning
confidence: 99%
“…Opioidergic SLP also augments protection via acute adenosine receptor activation (Peart et al ., ) and caveolin‐3 overexpression (See Hoe et al ., ). Importantly, SLP is effective in aged (Peart and Gross, ) and diabetic myocardium (See Hoe et al ., ) refractory to conventional protective stimuli, and also retains efficacy following 4 weeks of β‐adrenoceptor blockade whereas ischaemic preconditioning is lost under these conditions (See Hoe et al ., ).…”
Section: Pharmacological Induction Of Opioid Receptor‐mediated Cardiomentioning
confidence: 97%
“…The α‐adrenoceptor also influences cardioprotection, with evidence of impaired preconditioning in patients treated with the α‐adrenoceptor selective phentolamine (Tomai et al ., ). Our pilot data indicate that chronic (28 day) treatment with the β 1 ‐antagonist atenolol impairs intrinsic ischaemic tolerance and negates preconditioning‐dependent protection in murine tissue (See Hoe et al ., ). Nonetheless, protection via sustained opioid treatment appears resistant to these inhibitory effects.…”
Section: Confounding Impacts Of Ageing Co‐morbidities and Drugsmentioning
confidence: 97%
“…The role of β-agonism in cardioprotection is controversial, with many studies reporting protective and deleterious actions of both β 1 - [303,304,305,306,307] and β 2 -adrenoceptors [306,307,308,309,310] (β 1 - and β 2 -Ars, respectively) in the context of myocardial IRI. β-agonism that promotes Gs-PKA pathway activation is typically associated with myocardial damage, and activation of the Gi-ERK pathway is prosurvival; however, there are exceptions to this rule [305,308].…”
Section: Cardioprotection With Inotropic Supportmentioning
confidence: 99%
“…β-agonism that promotes Gs-PKA pathway activation is typically associated with myocardial damage, and activation of the Gi-ERK pathway is prosurvival; however, there are exceptions to this rule [305,308]. These mixed effects may reflect cardiac vs. extra-cardiac responses of β-ARs, variances in drug selectivity for β-AR subtype, and non-specific actions of β-AR responses [303]. Interestingly, a unique cardioprotective phenomenon termed sustained ligand-activated preconditioning (SLP) induces potent tolerance to IRI through regulation of the β 2 -AR-Gα s -PKA signaling pathway [308].…”
Section: Cardioprotection With Inotropic Supportmentioning
confidence: 99%